Recent Applications of TEMPO in Organic Synthesis and Catalysis - Varala, Ravi; Seema, Vittal (SynOpen, 2023)
In this spotlight article, authors highlighted the applications of TEMPO in organic synthesis and catalysis starting from 2015 to date.
Keywords: TEMPO; organic synthesis; catalysis; medicine; functional materials